The Reverse J-Shaped Association Between Serum Total 25-Hydroxyvitamin D Concentration and All-Cause Mortality: The Impact of Assay Standardization. Issue 8 (15th March 2017) - Durazo-Arvizu, Ramón A.; Dawson-Hughes, Bess; Kramer, Holly; Cao, Guichan; Merkel, Joyce; Coates, Paul M.; Sempos, Christopher T.
Abstract: We evaluated the impact of standardizing the originally measured serum total 25-hydroxyvitamin D (25(OH)D) values from Third National Health and Nutrition Examination Survey (NHANES III, 1988–1994) on the association between 25(OH)D and rate of all-cause mortality. Values were standardized to the gold-standard laboratory method. Follow-up from 1990–2006 consisted of 15, 099 participants aged at least 20 years at baseline, among whom there were 3, 784 deaths. Relative risk of death was adjusted for age, sex, race/ethnicity, and season using Poisson regression. Results were obtained for eight 25(OH)D (nmol/L) categories: <20 nmol/L, 20–29 nmol/L, 30–39 nmol/L, 40–49 nmol/L, 50–59 nmol/L, 60–74 nmol/L, 75–99 nmol/L (reference), and ≥100 nmol/L. Assay standardization dramatically shifted original 25(OH)D values toward zero. Accordingly, risk ≥120 nmol/L could not be evaluated (i.e., n  = 7 and n deaths  = 2). Relative risk (95% confidence interval (CI)) <40 nmol/L remained significant (30–39 nmol/L: relative risk (RR) = 1.4 (95% CI: 1.1, 1.6); 20–29 nmol/L: RR = 1.6 (95% CI: 1.3, 1.9), and <20 nmol/L: RR = 2.1 (95% CI: 1.6, 2.7). However, adjusted relative risk estimates for 25(OH)D levels ≥40 nmol/L were no longer significant (40–49 nmol/L: RR = 1.2 (95% CI: 0.99, 1.4); 50–59 nmol/L: RR = 1.2 (95% CI: 1.04, 1.4); 60–74 nmol/L: RR = 1.1 (95% CI: 0.94, 1.2); 75–99 nmol/L: RR = 1.0 (referent), and ≥100 nmol/L: RR = 1.1 (95% CI: 0.6, 2.1). In summary, after standardization, risk of death from all causes increased with decreasing 25(OH)D <40 nmol/L, while there was no association with values in categories between 40 nmol/L and 120 nmol/L.